Adding fish images taken in other countries to the biodiversity database of a Japanese public museum, with report of range extension of Labrisomus jenkinsi from the Pacific coast of Costa Rica - Miyazaki, Yusuke; Murase, Atsunobu; Sahara, Ryosuke; Angulo, Arturo [UNESP]; Senou, Hiroshi (Springer, 2017)
Many biodiversity databases have been launched in recent years. Various species of certain developed taxa, such as fish, quadrupeds, and butterflies, are currently able to be photographically identified, in particular for ecological and biogeographic studies. However, there are problems that result from registration of images from countries with different primary languages. In this study, we provide an example of the challenges associated with registering fish images, specifically one case that has functioned as a voucher for the range extension of Labrisomus jenkinsi (Heller and Snodgrass, 1903) (Perciformes: Labrisomidae) from the Galapagos Islands to the Pacific coast of Costa Rica. The fish image database in question belongs to a Japanese public museum [the Kanagawa Prefectural Museum of Natural History; the online version (FishPix) is provided by the museum and the National Museum of Nature and Science]. We propose that there are problems associated with image registration caused by using different languages. Furthermore, these challenges should be a common subject for discussion among museums as they attempt to accumulate biodiversity data from citizens in the future.
Keywords: Citizen science; Distribution; Documented record; Open science; Photograph